Network analysis of international trade in plastic scrap - Pacini, Henrique; Shi, Grace; Sanches Pereira, Alessandro; Silva Filho, Antônio Carlos (Elsevier, 2021)
This paper contributes to understanding the international trade of plastic scrap. This is done by structuring trade data in networks, and calculating network centrality indexes for countries engaged in plastic scrap trade, as well as for sub-types of plastic polymers (Ethylene, PVC, and Styrene). Network measurements allow insights on plastic scrap flows, as they identify important countries which concentrate material flows at scale, useful for technology dissemination, recycling infrastructure deployment, as well for standard-setting and negotiations. Network measurements based on 2018 data show the key role of EU and North American countries in the global plastic scrap trade network, with strong links to a few Asian countries. Developing regions such as South America, Africa, and Eurasia displayed discreet roles in the networks analyzed, indicating the need for more research on underreporting or other factors behind this apparent underrepresentation.